ENHANCING EFL LEARNING THROUGH AUTHENTIC MATERIALS: A DETAILED ANALYSIS OF IMPACT ON MOTIVATION AND PEDAGOGY (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: This paper explores the role of authentic materials in enhancing the quality of English language teaching (ELT) in EFL classrooms, with a particular focus on motivation and learner engagement. By incorporating real-world materials such as newspapers, films, and podcasts into language instruction, educators can bridge the gap between classroom learning and real-life language use. The paper reviews previous studies, including those by Guariento and Moriey (2001), Peacock (1997), and Nuttall (1996), while also presenting new findings from a detailed investigation conducted in a local EFL context. The results reveal that authentic materials not only improve language skills, particularly in reading comprehension, but also significantly boost student motivation. The paper concludes by discussing how teachers can integrate these materials effectively into their curriculum while addressing challenges.